2017
DOI: 10.1111/1462-2920.13613
|View full text |Cite
|
Sign up to set email alerts
|

The septin protein Sep4 facilitates host infection by plant fungal pathogens via mediating initiation of infection structure formation

Abstract: Many phytopathogenic fungi use infection structures (IFSs, i.e., appressoria and infection cushions) to penetrate host cuticles. However, the conserved mechanisms that mediate initiation of IFS formation in divergent pathogens upon sensing the presence of host plants remain obscure. Here, we demonstrate that a conserved septin gene SEP4 plays crucial roles in this process. Disruption of SEP4 in the plant grey mould fungus Botrytis cinerea completely blocked IFS formation and abolished the virulence of ΔBcsep4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(101 citation statements)
references
References 73 publications
4
97
0
Order By: Relevance
“…S9). Consistent with our previous findings (Feng et al ., ), inhibition of ROS production by exogenous DPI, a flavoprotein inhibitor that blocks ROS production by NADPH oxidases (Nox) (Chandel et al ., ), greatly reduced ROS production in hyphal ends or mycelia forming infection structures (Supporting Information Fig. S9).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S9). Consistent with our previous findings (Feng et al ., ), inhibition of ROS production by exogenous DPI, a flavoprotein inhibitor that blocks ROS production by NADPH oxidases (Nox) (Chandel et al ., ), greatly reduced ROS production in hyphal ends or mycelia forming infection structures (Supporting Information Fig. S9).…”
Section: Resultsmentioning
confidence: 99%
“…5F and G). Trypan blue staining analysis (Feng et al, 2017) demonstrated that the mutant conidia could germinate normally on the host leaf surfaces. However, they failed to penetrate into host tissue (Supporting Information Fig.…”
Section: Nop53 Controls Virulence Of B Cinereamentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivities of the tested strains to different stresses were analyzed as previously described (Feng et al ., ). Briefly, conidial suspension (1 μl, 1 × 10 6 conidia ml −1 ) or mycelial plugs (5 mm in diameter) of the B. cinerea WT, Δ Bcpck1 mutant and complemented strains were inoculated onto CM supplemented with different concentrations of stress agents, including osmotic stress agents NaCl and KCl, oxidative stress reagent H 2 O 2 and cell wall disturbing agents SDS and Congo Red.…”
Section: Methodsmentioning
confidence: 97%